Record of five alien species of Decapod Crustaceans for the first time in the Syrian Marine Water - علو آلاء; ازدهار عمار; حديثة كشيري (Latakia University Journal -Biological Sciences Series, 2022)
During several cruises, benthic samples were collected from the coastal area in Ras Al-Bassit (north of Lattakia) and the AL-Ahlam beach (south of Tartus) in the year 2021, five species of small, non-indigenous crustaceans were founded: Alpheus amblyonyx, Synalpheus dardeaui, Xantho pilipes, Pachygrapsus planifrons, Pinnotheres pisum, in association with sponges and Mussels from infralittoral zone. These species are native to the Atlantic, Indian and Pacific oceans. It is the first record of these species in Syria and eastern mediterranean, their presence north and south of the Syrian coast indicates their spread and settlement in the Syrian marine environment.